The big 5 leagues: The determinants of football transfer fees - Martins, Henrique Miguel Sequeira (2021)
This study aims to identify which determinants have a significant effect on football transfer fees, in the 2019/2020 summer transfer market, and for the European Big 5 leagues, using a sample of 436 individual transfers. Following Ante´s work (2019), the analysis is conducted through stepwise regression with backwards elimination with an elimination measure of p >= .2. The study identifies players’ and performance characteristics, contract duration, the domestic league players are transferred to, and playing position as the determinants of transfer fees which have a positive or negative effect. Minutes Played, Goals, Through Balls, Contract Duration, Premier League and Strikers are some of the main determinants which show a positive effect on transfer fees. On the other hand, Age (squared), Fouls, Clearances and Central Defender present a negative impact. Furthermore, differences across the sub-samples concerning the Big 5 leagues, transfer size and playing position can be identified which suggests that the overall results, that is, the results from the full sample might not be the right path in terms of statistical analysis for determinants of transfer fees.